2011
DOI: 10.1039/c0nr00840k
|View full text |Cite
|
Sign up to set email alerts
|

Self-folding and aggregation of amyloid nanofibrils

Abstract: Amyloids are highly organized protein filaments, rich in beta-sheet secondary structures that self-assemble to form dense plaques in brain tissues affected by severe neurodegenerative disorders (e.g. Alzheimer's Disease). Identified as natural functional materials in bacteria, in addition to their remarkable mechanical properties, amyloids have also been proposed as a platform for novel biomaterials in nanotechnology applications including nanowires, liquid crystals, scaffolds and thin films. Despite recent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 54 publications
2
69
0
Order By: Relevance
“…It has been recently shown that the end-capped heptapeptide CH 3 CONHbAbAKLVFF-CONH 2 , modified from the Ab (16)(17)(18)(19)(20) fragment KLVFF, 23 assembles upon incubation into different morphologies of amyloid fibrils from twisted ribbons to helical ribbons and finally to nanotube-like structures. 24 Due to the different area moment of inertia I for the three packing schemes we do expect a different persistence length for the three structures, which we estimate (from fibrils with identical height profile and same maximum height), using the bond correlation function hcosq(s)i ¼ exp(Às/2l p ) where q is the angle between the tangent vectors to the chain at two points separated by a contour distance s and the factor 2 is used to rescale the exponential decay accounting for the two-dimensional nature of fibrils absorbed on a substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently shown that the end-capped heptapeptide CH 3 CONHbAbAKLVFF-CONH 2 , modified from the Ab (16)(17)(18)(19)(20) fragment KLVFF, 23 assembles upon incubation into different morphologies of amyloid fibrils from twisted ribbons to helical ribbons and finally to nanotube-like structures. 24 Due to the different area moment of inertia I for the three packing schemes we do expect a different persistence length for the three structures, which we estimate (from fibrils with identical height profile and same maximum height), using the bond correlation function hcosq(s)i ¼ exp(Às/2l p ) where q is the angle between the tangent vectors to the chain at two points separated by a contour distance s and the factor 2 is used to rescale the exponential decay accounting for the two-dimensional nature of fibrils absorbed on a substrate.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, estimations of Young's moduli of amyloid fibrils by simulations point at numbers in the same order of magnitude as experimental values, yet, systematically higher. [18][19][20][21] Recently, we have reported that peak force quantitative nanomechanical (PF-QNM) AFM shows great potential to be applied as a high-resolution technique to identify structural features and associated nanomechanical properties of amyloid fibrils. 22 Here we further demonstrate that the technique is insensitive to the structural details of the amyloid fibril cross-section, that is to say that the intrinsic stiffness expressed by Young's modulus can be correctly de-coupled from the overall rigidity, to which both Young's modulus and cross-section contribute.…”
Section: Introductionmentioning
confidence: 99%
“…These so-called coarse-grained models are powerful techniques that can reach scales of tens of micrometers. The inlay in Figure 2 shows how such coarse-graining can be done for an amyloid fibril for the case of an amyloid plaque model [9], and illustrates how hundreds of atoms are grouped into particles. Since all parameters in this coarse-grained model can be determined based on full atomistic models there is no need to introduce empirical parameters.…”
Section: A Materiomics Approachmentioning
confidence: 99%
“…The inlay shows the multiscale approach as applied to a model of amyloid fibrils and plaques, where a systematic coarse-graining from atomistic-level fibrils, to a bead model, to a plaque model is used to bridge the scales from Angstrom to micrometers [9].…”
Section: Figures and Captionsmentioning
confidence: 99%
“…In vivo they rarely exist as isolated single filaments, but they rather further entangle into percolating networks first and amyloid plaques and deposits afterwards, all with multiple characteristic length scales [1,3]. These structures initially identified in nature, in the context of pathological protein-prone neurodegenerative diseases, have also been discovered as key functional components in biological organisms ranging from bacteria to humans [1,4,5].…”
mentioning
confidence: 99%